Pengaruh Self-Enhancement, Conservation Atas Budaya Pajak Pribadi Dengan Di Moderasi Tingkat Penghasilan - Septian, Irfan; Indrati, Menik (Owner : Riset dan Jurnal Akuntansi, 2024)
This research investigates the influence of Self-Enhancement and Conservation on personal tax culture, by considering income level as a moderating factor. Involving employees at the Ministry of Law and Human Rights in West Java as research subjects, this research aims to understand how the encouragement to increase a positive view of oneself Self-Enhancement and conservation values (Conservation) contributes to the formation of attitudes and behaviour regarding tax obligations. The respondents in this research were 230 employees at the Ministry of Law and Human Rights in West Java. Data analysis uses Structural Equation Model (SEM). The research results show that Self-Enhancement and Conservation have a positive influence on personal tax culture. Furthermore, income level was identified as a significant moderator, able to strengthen the relationship between these factors and personal tax culture. Managerial implications involve developing strategies that combine Self-Enhancement and Conservation in training and tax policy, with tailored adjustments to individual financial conditions, to build a sustainable tax culture in the organization.